Use of gold nanoparticle-silibinin conjugates: A novel approach against lung cancer cells - Ravi, Rangnath; Zeyaullah, Md.; Ghosh, Shubhrima; Khan Warsi, Mohiuddin; Baweja, Renu; AlShahrani, Abdullah M.; Mishra, Abhijeet; Ahmad, Razi (Frontiers in Chemistry, 2022)
Lung cancer presents one of the most challenging carcinomas with meager 5-year survival rates (less than 20%), high metastasis and high recurrence due to chemo- and radio- resistance. An alternative or complementation to existing prognosis modalities is the use of phytochemicals such as silibinin, which targets essential cytokines, angiogenic factors and transcription factors for a profound anti-tumor effect. However, the problems of low solubility in an aqueous physiological environment, poor penetration, high metabolism and rapid systemic clearance limit the therapeutic use of silibinin. Conjugation of gold nanoparticles (GNPs) with silibinin may overcome the above challenges along with distinct advantages of biocompatibility, optical properties for monitoring and causation of cytotoxicity in cancer cells. The current study thus aims to develop silibinin conjugated gold nanoparticles (Sb-GNPs) with pH responsive release in the cancer microenvironment, optimizing several parameters for its higher activity and further evaluate the nanoplatform for their efficacy in inducing cell death in vitro against A549 lung cancer cells. GNPs was synthesized using trisodium citrate dihydrate as the reducing agent and further used for the conjugation of silibinin. The synthesized GNPs were found to be monodispersed and spherical in shape. The silibinin was successfully conjugated with gold nanoparticles and long-term stability of GNPs and Sb-GNPs nanoconjugates in suspension phase was confirmed by FTIR and DLS. Anticancer properties of Sb-GNPs were confirmed by different assay using MTT, Trypan blue dye exclusion assay and cell cycle analysis assay. After conjugation of silibinin with GNPs, the efficacy of silibinin increased 4–5 times in killing the cancer cells. This is the first report on using silibinin gold nanoconjugate system for lung cancer therapy with promising future applications.